Antioxidant, Phytotoxic and Antimicrobial Activities of Methanolic Extract of Bauhinia variegata Barks - Sharma, Khaga Raj; Kalauni, Surya Kant; Awale, Suresh (Journal of Institute of Science and Technology, 2015)
Bauhinia variegata is well-known medicinal plant used from the ancient era to till date for their medicinal values. The methanolic extract of Bauhinia variegata barks was screened for phytochemical constituents, antioxidant, phytotoxic and microbial activity. The microbial activity was tested against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhi at different concentration of 10, 15 and 20 mg/mL by agar well diffusion method. The plant extract showed the potent antimicrobial activity against the Staphylococcus aureus, Salmonella typhi, Bacillus subtilic and Escherichia coli with zone of inhibition 14 mm, 12mm, 14mm and 11mm respectively. Phytochemical analysis of the extract revealed that the antioxidant and antimicrobial activity of the plant materials is due to the presence of active secondary metabolites. In DPPH free radical scavenging assay the IC50 value of Bauhinia variegata was found to be 6.48±0.08 ?g/mL, while the IC50 value of the reference standard ascorbic acid was 45.93?g/mL. The extract of Bauhinia variegata, contains high value of phenolic (156.30±0.3 mg GAE/gm) and flavonoid (16.04±1.4 mg QE/gm) content exhibited the high antioxidant activity. The in-vitro phytotoxic bioassay showed 65%, 40%, and 25% growth regulation at just higher conc. of 1000, 100 and 10 ?g/mL with number of fronds 07, 12 and 15 respectively with respect to standard drug Paraquat of concentration 0.015?g/mL. Journal of Institute of Science and Technology, 2015, 20(2): 37-41